Does Male Skin Care Content on Instagram Neglect Skin Cancer Prevention? - Alexa Carboni; Olnita Martini; Jessica Kirk; Nathaniel A Marroquin; Corinne Ricci; Melissa Cheng; Mindy D Szeto; Kayd J Pulsipher; Robert P Dellavalle (JMIR Dermatology, 2024)
This research letter assesses male skin care content on social media in order to bring to light the lack of content regarding skin cancer prevention posted on Instagram for male audiences.